2012
DOI: 10.1242/jeb.073593
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific recognition of the carrier insect by dauer larvae of the nematode Caenorhabditis japonica

Abstract: SUMMARYHost recognition is crucial during the phoretic stage of nematodes because it facilitates their association with hosts. However, limited information is available on the direct cues used for host recognition and host specificity in nematodes. Caenorhabditis japonica forms an intimate association with the burrower bug Parastrachia japonensis. Caenorhabditis japonica dauer larvae (DL), the phoretic stage of the nematode, are mainly found on adult P. japonensis females but no other species. To understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…C. elegans shares with a number of other Caenorhabditis the trait of generalism toward invertebrate dispersal hosts, albeit not entirely promiscuous in host use [2,5,7]. However, the specialized relationship of C. japonica with the hemipteran insect Parastrachia japonensis provides the best understood natural history of any species [25,26]. It is plausible that C. drosophilae, which appears to disperse solely on Drosophila nigrospiracula to new cactus rots [27], and some other less well-understood Caenorhabditis, also evolved specialized dispersal host relationships from a more generalist ancestral state.…”
Section: How Does Ecology Define Caenorhabditis Biodiversity?mentioning
confidence: 99%
See 2 more Smart Citations
“…C. elegans shares with a number of other Caenorhabditis the trait of generalism toward invertebrate dispersal hosts, albeit not entirely promiscuous in host use [2,5,7]. However, the specialized relationship of C. japonica with the hemipteran insect Parastrachia japonensis provides the best understood natural history of any species [25,26]. It is plausible that C. drosophilae, which appears to disperse solely on Drosophila nigrospiracula to new cactus rots [27], and some other less well-understood Caenorhabditis, also evolved specialized dispersal host relationships from a more generalist ancestral state.…”
Section: How Does Ecology Define Caenorhabditis Biodiversity?mentioning
confidence: 99%
“…Moreover, dauer larvae participate in nictation behavior -they climb up substrate protrusions, standing on their tails and waving, often forming large ropy and wriggling aggregates of thousands of worms -that facilitates adhesion to and transport by dispersal vectors [2,13,31]. Invertebrate vectors appear common, albeit with few examples of flight-capable hosts [2,3,26], and frugivorous vertebrates might also contribute to Caenorhabditis natural dispersal. More recently, commercial human agriculture likely provides a means of movement, especially for cosmopolitan species such as C. elegans, C. briggsae, and C. brenneri.…”
Section: A D Cuttermentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to pollinating wasps, who must enter the -associated and tend to be promiscuous in carrier choice [51] (although some preferences in C. remanei have been noted [88]). The more distantly-related C. japonica has been shown to have behavioral preferences for its shield bug host [89], and similar findings have been shown for Pristionchus nematodes and their host beetles [90]. Nematode occupancy biases on pollinating wasps relative to parasitic wasps have been observed in the figassociated parasitic Schistonchus and Parasitodiplogaster nematodes [45,91].…”
Section: Discussionmentioning
confidence: 63%
“…In our previous study, we demonstrated that C. japonica DL specifically embark on P. japonensis and are attracted to the hexane extracts containing body surface components of P. japonensis (Okumura et al, 2013a). These studies indicate the presence of a species-specific kairomone that is directly released by the host insect and attracts DL.…”
Section: Short Communicationmentioning
confidence: 86%